Beyond Habitat: Memory Versus Environment in Shaping Animal Space Use - Tana L. Verzuh; Kevin L. Monteith; Tayler N. LaSharr; Cody F. Wallace; Rachel A. Smiley; Brittany L. Wagler; Chris Geremia; Katey S. Huggler; Hall Sawyer; Matthew J. Kauffman; Jerod A. Merkle (Ecology Letters, 2025)
For nearly half a century, ecologists have sought to explain animal space use through characteristics of the environment (i.e., habitat). Recent evidence suggests animals also use memory of previous experiences to decide when and where to move. Yet, the relative influence of the two in explaining animal space use has not been resolved. Using six large ungulate species in the Rocky Mountains (USA), we evaluated the performance of a habitat selection model with 16 environmental variables and another with two variables representing previous use (i.e., memory). While memory outperformed the environment for two species and the environment outperformed memory for four species, the influence of memory and the environment was overall comparable. The environment best explained the space use of specialists, while memory best explained species with strong site fidelity. Our work challenges traditional habitat selection theory, showcasing that animals build their spatial preferences through experience just as much as merely responding to their environment.